Metformin attenuates alveolar bone destruction in mice with apical periodontitis and inhibits pro-inflammatory cytokine synthesis in lipopolysaccharide-stimulated RAW264.7 through the AMPK-mTOR-NF-κB pathway - Ren, Chunmei; Tazawa, Kento; Kawashima, Nobuyuki; Ohshima, Risa; Okada, Yamato; Wang, Shihan; Yu, Ziniu; Han, Peifeng; Ohsugi, Yujin; Katagiri, Sayaka; Okiji, Takashi (Frontiers in Immunology, 2025)
IntroductionApical periodontitis, caused by bacterial infection through the root canals, is characterized by chronic inflammation and bone resorption around the root apex. Metformin, a first-line therapeutic drug for type 2 diabetes mellitus, has attracted attention for its potential anti-inflammatory properties and role in regulating bone homeostasis. The hypothesis in this study was that metformin inhibits bone destruction in apical periodontitis by suppressing macrophage-mediated inflammatory responses. The aim of this study was to evaluate the effect of systemic metformin administration on experimentally induced apical periodontitis development in an animal model and clarify the underlying anti-inflammatory mechanism of metformin in lipopolysaccharide-stimulated mouse macrophages.MethodsEvaluations on the effects of metformin on the progression of periapical lesions were conducted in experimentally induced mouse apical periodontitis in vivo, and its anti-inflammatory effects in lipopolysaccharide-stimulated RAW264.7 macrophages in vitro were analyzed.ResultsMetformin significantly reduced periapical bone destruction on postoperative days 21 and 28, and decreased the number of osteoclasts on the periapical alveolar bone on postoperative day 28. It also suppressed pro-inflammatory cytokine expression and nuclear factor kappa B signaling in lipopolysaccharide-stimulated RAW264.7. RNA-sequencing data revealed the downregulation of the mammalian target of rapamycin signaling after metformin treatment, which was confirmed by the downregulation of the mammalian target of rapamycin phosphorylation by metformin. Furthermore, metformin activated adenosine monophosphate-activated protein kinase, a potent negative regulator of mammalian target of rapamycin complex 1. The suppression of inflammatory cytokine expression by metformin was abolished by compound C, a potent adenosine monophosphate-activated protein kinase inhibitor.DiscussionThis study revealed that metformin suppressed inflammatory bone destruction in periapical lesions. The mechanism partially involves inhibiting the mammalian target of rapamycin/nuclear factor-kappa B signaling in macrophages through adenosine monophosphate-activated protein kinase signaling activation. Findings from this study show that metformin has therapeutic potential in inflammatory bone destruction, such as apical periodontitis.